2016
DOI: 10.1089/aid.2015.0281
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of In Utero Antiretroviral Exposure: Systolic and Diastolic Function in HIV-Exposed Uninfected Youth

Abstract: The aim of this study was to evaluate the association of in utero exposure to highly active antiretroviral therapy (HAART) with left ventricular (LV) function and structure in HIV-exposed uninfected (HEU) children. A prospective, multisite cohort study in HEU children was conducted by the Pediatric HIV/AIDS Cohort Study (PHACS). Echocardiographic measures of LV systolic and diastolic function and cardiac structure were obtained from HEU subjects aged ‡6 years enrolled in the PHACS Surveillance Monitoring of AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Chronic inflammation is associated with LV diastolic dysfunction and heart failure in HIV-infected children and adults. 4648 In HIV-infected patients with myocarditis, a complex interaction between HIV and other cardiotropic viruses, IL-1, IL-6, TNF-α, and suppression of the anti-inflammatory cytokine IL-10 may explain the cardiotoxic effects leading to dilated cardiomyopathy. 4950…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is associated with LV diastolic dysfunction and heart failure in HIV-infected children and adults. 4648 In HIV-infected patients with myocarditis, a complex interaction between HIV and other cardiotropic viruses, IL-1, IL-6, TNF-α, and suppression of the anti-inflammatory cytokine IL-10 may explain the cardiotoxic effects leading to dilated cardiomyopathy. 4950…”
Section: Discussionmentioning
confidence: 99%
“…HEU children are mainly considered a healthy population, although recent studies have raised concerns regarding their cardiovascular health. Several studies have demonstrated significant changes in the cardiovascular structure and function of HEU offspring from fetal life to adolescence [712]. A recent study by our group suggested that fetal cardiac remodeling observed in HIV-infected pregnancies was associated with maternal use of zidovudine [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, should they become inefficient, mtDNA deletions observed herein are likely to contribute, at least partially, to the health impairments observed in HEU children, especially those with increased deletion contents. It is striking that cardiac conduction dysfunctions, muscle weakness, or elevated lactate concentrations reported in HEU children [ 45 , 46 , 47 ] are also hallmarks of most mitochondrial disorders.…”
Section: Discussionmentioning
confidence: 99%